2023
DOI: 10.1155/2023/5782656
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antibacterial and Antibiofilm Effects of Ethyl Acetate Root Extracts from Vernonia adoensis (Asteraceae) against Pseudomonas aeruginosa

Abstract: There is an increase in mortality and morbidity in the health facilities due to nosocomial infections caused by multidrug-resistant nosocomial bacteria; hence, there is a need for new antibacterial agents. Vernonia adoensis has been found to possess medicinal value. Plant phytochemicals may have antimicrobial activity against some resistant pathogens. The antibacterial efficacy of root extracts against Staphylococcus aureus and Pseudomonas aeruginosa was investigated using the microbroth dilution method. All e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…For instance, reports on the EOs from Tagetes minuta , cinnamon oil, Thymus daenensis , and Satureja hortensis found that they effectively prevented the production of biofilms, as well as other virulence factors mediated by QS [ 31 , 39 , 40 ]. Plants belonging to the same family as M. aurea have been reported to have antibiofilm activity, such as Launaea capitata [ 41 ], Helichrysum caespitium [ 42 ], and Vernonia adoensis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, reports on the EOs from Tagetes minuta , cinnamon oil, Thymus daenensis , and Satureja hortensis found that they effectively prevented the production of biofilms, as well as other virulence factors mediated by QS [ 31 , 39 , 40 ]. Plants belonging to the same family as M. aurea have been reported to have antibiofilm activity, such as Launaea capitata [ 41 ], Helichrysum caespitium [ 42 ], and Vernonia adoensis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%